Assessing the Quality of Care Provided to Pediatric Patients by Emergency Room Physicians - Wachsman, Laura (1983)
Although the number of children seen in emergency rooms for nonemergency problems is increasing, relatively few of the physicians who staff such facilities are specialists in pediatrics. For this reason, it is important to evaluate the care that children receive in emergency rooms. A retrospective review of 450 charts was done, using implicit criteria for evaluating the process of care, to assess the quality of care provided to children seen by nonpediatricians in an emergency room. A schema of 15 categorical errors was used to record deficiencies in the charts of these patients. Errors were found in one or more of these categories in 54.4 percent of these charts. Errors in the category of drug prescription, especially in dosage, were the most frequent. These findings may indicate inadequate preparation of emergency room physicians to care for the common problems of pediatric patients and may justify additional pediatric training for physicians who will be providing care to children in emergency rooms.